Le paysage irlandais, un espace photogénique : réflexions autour de quelques séries photographiques en Irlande - Pierre-Jérôme Jehel; Corinne Feiss-Jehel (Revue LISA)
Ireland is known to be a photogenic country. Yet it seems that verdant Ireland and its rugged coastlines have been turned into clichés and dominant visual stereotypes which are deemed to represent the only true and authentic landscapes of Ireland. Basing our study on three photographic series by the authors, we shall explore landscape as a form of language in which the notion of framing reflects an aesthetic and a scientific choice. While the photographer tries to capture his perception of the landscape, the geographer develops an analytical description. Here, the Irish landscape is treated as a testing ground for both views. This paper will move from individual observations towards a diversified approach to the plurality of aesthetic readings.